MENENTUKAN TINGKAT KEMACETAN LALULINTAS DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Yusuf Ramadhan Nasution (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2017)
Traffic density in the city of Medan, especially in the District of Medan City, has caused serious problems in various fields such as impaired travel comfort, travel boredom, travel fatigue, waste of time and material. With some of these problems, a decision support system is needed that can help reduce traffic congestion. In the decision-making process involving many criteria and many alternatives, the Analytical Hierarchy Process (AHP) method is often used as a problem-solving method. Decision-making is done by giving the value of perception as weighted by a decision maker or expert. The results of this study is the establishment of a decision support system to determine the level of traffic congestion in Medan City Sub-district by using AHP so as to provide an information for the users of the road to reduce the congestion level in the future. Keywords: Congestion, traffic, District of Medan City, Decision support system, AHP.